Is Institutional Research on Management Accounting Degenerating or Progressing? A Lakatosian Analysis. (3rd August 2022) - Modell, Sven
ABSTRACT: Adopting a Lakatosian perspective, this paper asks whether management accounting (MA) research using institutional theory can be described as a degenerative or progressive research program. Motivated by similar critical debates about the larger institutional research program in organization studies, I map the evolution of institutional research on MA with an eye to its theoretical contributions to the accounting literature as well as this larger research program. I conclude that this body of research has offered important, progressive extensions to the accounting literature and, to a lesser extent, the larger institutional research program. However, there is also evidence of many MA scholars using institutional theory in ways that produce degenerative tendencies. These degenerative tendencies are, in large part, due to the persistent proclivity of researchers to place overly one‐sided emphasis on the role of either human agency or preexisting institutions in explaining the process of (de‐)institutionalization and may, at worst, cause functionalist assumptions to be smuggled back into institutional analyses in ways that threaten the hard core of the institutional research program. I discuss how these tendencies can be rectified in future research and how institutional research on MA can be further developed. RÉSUMÉ: La recherche institutionnelle sur la comptabilité de gestion est‐elle en train de dégénérer ou de progresser? Une analyse lakatosienne En adoptant une perspective lakatosienne, cet article examine si la recherche en comptabilité de gestion utilisant la théorie institutionnelle peut être décrite comme un programme de recherche dégénératif ou progressif. Motivé par des débats critiques similaires concernant le vaste programme de recherche institutionnelle sur les études organisationnelles, l'auteur trace l'évolution de la recherche institutionnelle en comptabilité de gestion en tenant compte de ses contributions théoriques à la littérature comptable ainsi qu'à ce vaste programme de recherche. L'auteur montre que cet ensemble de recherches a intégré des développements importants et progressifs à la littérature comptable et, dans une moindre mesure, au vaste programme de recherche institutionnelle. Cependant, les résultats de l'étude indiquent que de nombreux chercheurs en comptabilité de gestion utilisent la théorie institutionnelle de manière à nourrir des tendances dégénératives. Ces tendances dégénératives sont, en grande partie, dues à la tendance persistante des chercheurs à mettre l'accent de manière trop unilatérale sur le rôle du facteur humain ou des institutions préexistantes dans l'explication du processus de (dé)institutionnalisation et peuvent, dans le pire des cas, provoquer le retour des hypothèses fonctionnalistes dans les analyses institutionnelles de manière à menacer le noyau dur du programme de recherche institutionnelle. L'auteur examine comment ces tendances peuvent être contrées dans les recherches futures et comment la recherche institutionnelle en comptabilité de gestion peut être développée davantage.